Handover in DVB-H Investigation and Analysis - Yang, Xiaodong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book gives a detail description of the handover issues in DVB-H networks, in converged DVB-H/UMTS networks and in hybrid DVB-H/DMB-T networks. Besides, the DVB-H signalling information including ESG is discussed. The current status and the future research directions of DVB-H and DVB-H handover are presented so that the readers can also get an overview of the research methods being used. Although this book is research focused, it also gives a detail introduction to the basic concepts such as handover, time slicing, ESG, etc.. This book is written in a way that even people without prior knowledge of DVB-H can easily understand. At the end of each chapter there are some questions and there are solutions to those questions at the end of the book. This book can be used by researchers, engineers, academics, regulatory bodies and business managers as a reference book, or by university students as a text book or a reference book.
Motivation and Approaches -- Survey of Handover Research in DVB-H -- DVB-H Signalling Information -- Electronic Service Guide -- Handover Algorithm for a Dedicated DVB-H Network -- Post Processing of SNR Based Handover -- Repeater Aided Soft Handover -- Repeater Aided Soft Handover Probability -- Handover Algorithm for Converged Networks -- Handover Algorithm for Hybrid Broadcast Networks -- Conclusions and Future Work.
Keywords: Engineering; Input-output equipment (Computers).; Coding theory; Microwaves; Optical engineering; Electrical engineering; Engineering; Signal, Image and Speech Processing; Input/Output and Data Communications; Communications Engineering, Networks; Coding and Information Theory; Microwaves, RF and Optical Engineering; Electronic books